On the Hegelianism of the “Neo-Hegelians”: Edward Caird and Francis Herbert Bradley - Uchan, Alexandre (Roczniki Filozoficzne, 2025)
The purpose of this paper is to examine the widely held belief that the so-called British Idealist movement was in fact a continuation of Hegelian idealism. As I try to show in the paper, the question of the Hegelianism of the British Idealists is not straightforward, for the British Idealist movement itself was not philosophically homogeneous. In order to demonstrate this heterogeneity, I will juxtapose the views of two British idealists who seem to occupy extreme positions when it comes to their attitude towards Hegel: Edward Caird and Francis Herbert Bradley. As I point out, Caird explicitly referred to the thought of the German idealist, developing on its basis his own philosophy whose chief problematic was social and political. On the other hand, Bradley – often regarded as the main representative of the movement – explicitly dissociated himself from Hegel’s philosophy (while emphasising its value), pointing to its theoretical limitations. What Bradley could not agree to was, above all, Hegelian panlogism and the dynamic conception of the Absolute.